Finite element brain deformation in adolescent soccer heading - Huber, C. M.; Patton, D. A.; Maheshwari, J.; Zhou, Z.; Kleiven, S.; Arbogast, K. B. (Computer Methods in Biomechanics and Biomedical Engineering, 2024)
Finite element (FE) modeling provides a means to examine how global kinematics of repetitive head loading in sports influences tissue level injury metrics. FE simulations of controlled soccer headers in two directions were completed using a human head FE model to estimate biomechanical loading on the brain by direction. Overall, headers were associated with 95th percentile peak maximum principal strains up to 0.07 and von Mises stresses up to 1450 Pa, and oblique headers trended toward higher values than frontal headers but below typical injury levels. These quantitative data provide insight into repetitive loading effects on the brain.